Investigation of magnetic field measurements recorded by low earth orbiting satellites - Thomas, Neethal (Indian Institute of Geomagnetism (IIG), 2016)
The thesis concentrates on the following problems. 1. The study of the global features of EEJ current parameters derived from Swarm satellites during quiet geomagnetic conditions. 2. The study of the magnetic field variations recorded by Swarm satellites during geomagnetic storms. 3. Investigation of impulsive ULF oscillations in the frequency range 6.6-25 mHz termed as Pi2 pulsations associated with substorm phenomenon. 4. To examine the occurrence of daytime Pi2 in the topside ionosphere and understand its source mechanism. 5. Investigation of inherent spatial frequencies present in the total magnetic field measure ments at LEO satellites during quiet geomagnetic conditions and its possible interference with temporal oscillations of similar frequencies.
A thesis submitted to the University of Mumbai for the Ph.D.(Science) degree in physics under the guidance of Dr. Geeta Vichare
Keywords: CHAMP satellite; Magnetosphere; Equatorial electrojet (EEJ); Magnetic field; Satellite; PhD Thesis